Administrative Creativity among Secondary School Principals from the Teachers' Point of View - Rashid Al-Mashhadani, Asia Hamid; Aziz Al-Khashmani, Awan Kazem (Journal of Tikrit University for Humanities, 2024)
The primary objective of the present study is to ascertain the extent to which secondary school administrators engage in administrative innovation, as seen by teachers. This study examines the statistically significant variations in administrative inventiveness among secondary school administrators, as seen by teachers, based on the gender variable (male - female). This study examines the statistically significant variations in administrative inventiveness among secondary school administrators, as seen by teachers, based on different years of service (1-5 years), (10-6 years), and (10 years or more). The study group comprised educators from secondary schools, while the research sample encompassed a total of 200 male and female instructors. The scale for measuring administrative creativity was constructed by the researcher, with five distinct possibilities (always, frequently, sometimes, rarely, never). This scale has been refined to its final version, consisting of a total of 25 questions. The researcher used the approach of re-testing and obtained a series of findings, which are as follows: 1- Teachers perceive the level of administrative inventiveness among secondary school administrators to be moderate. According to the gender variable, there are statistically significant disparities in the administrative inventiveness of secondary school administrators as seen by teachers, with a preference for men. According to the variable of years of service, there are statistically significant disparities among secondary school principals in relation to instructors, with a preference for the group of 15 years of service.